1951
DOI: 10.1021/ja01156a041
|View full text |Cite
|
Sign up to set email alerts
|

In Situ X-Ray Diffraction Studies of Heterogeneous Reactions1

Abstract: Dec., 19511% Situ X -R A Y DIFFRACTION STUDIES OF HETEROGENEOUS KEACTIONS 5635 lakes. The lakes formed by additlg a drop of a solution containing at least 0.2 mg./ml. of the respective dyes to a little solid palladium(I1) cyanide on a piece of filter paper are dark blue and red-pink, respectively. Hence it is easy to differentiate between drops of solutions which contain at least approximately 0.2 mg. of dye par milliliter.Palladium( 11) cyanide also forms adsorption complexes with many alkaloids. Dilute hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1953
1953
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This diagram should be compared with the corresponding one, Fig. The more gradual increase of the critical partial pressure of the CO with increasing temperature given by 119. Fig.…”
Section: Temperature In °Cmentioning
confidence: 95%
“…This diagram should be compared with the corresponding one, Fig. The more gradual increase of the critical partial pressure of the CO with increasing temperature given by 119. Fig.…”
Section: Temperature In °Cmentioning
confidence: 95%
“…The authors' views on the direct reduction of magnetite to metallic iron are divided. Authors of the work [1], on the basis of "in situ" examinations carried out in a reaction chamber, made with the aid of XRD method, confirmed the presence of wustite after the reduction at a temperature of 413 • C. Other authors on the ground of chemical analysis and Mössbauer investigations [37,38] made the wustite formation impossible during the reduction of the magnetite precursor. Results of our research confirmed that magnetite was reduced to iron through the wustite phases.…”
Section: Catalysts 2018 8 X For Peer Review 3 Of 12mentioning
confidence: 99%
“…The formation of wustite under conditions where wustite is metastable has been reported from magnetic measurements during reduction [106][107][108] and from X-ray powder diffraction [109] during reduction. Evidence against the formation of wustite has been reported from chemical analysis [110] and Mossbauer spectroscopic studies [27,111].…”
Section: Bulk Structurementioning
confidence: 99%